Metadata from mooring F4-W-4 in the Fram Strait, July 2022 – June 2023 - Mario Hoppmann; Wilken-Jon von Appen; Jacob Allerholt; Rainer Graupner; Jonas Hagemann; Morten Hvitfeldt Iversen; Christian Konrad; Normen Lochthofen; Janine Ludszuweit; Rebecca McPherson; Matthias Monsees; Simon F Reifenberg; et al. (PANGAEA, 2025)
Time-series data of physical oceanography and carbon/particle export were obtained from mooring F4-W-4 in the Fram Strait from, July 2022 – June 2023 as part of the Helmholtz infrastructure program Frontiers in Arctic Marine Monitoring (FRAM) legacy and the long-term monitoring program at AWI HAUSGARTEN. The mooring was deployed during RV POLARSTERN expedition PS131, and recovered during PS136. For this mooring, only the metadata is available here. The profiling winch (nominal depth: 132m) did not record any valid data due to technical issues. The mooring also included one BioOptical Platform (nominal depth: 427m; data archived elsewhere). Auxiliary information such as sensor calibration sheets, mooring diagrams and schedule files are also provided, if applicable.
In: Hoppmann, Mario: Collection of raw data from oceanographic moorings in the Fram Strait, Greenland Sea, and central Arctic Ocean, 2018-2025 [dataset publication series]. PANGAEA, https://doi.pangaea.de/10.1594/PANGAEA.959812 (dataset in review)